A Tale of Two Bases: Progressive Taxation of Capital and Labor Income. (May 2021) - Moore, Rachel; Pecoraro, Brandon
Macroeconomic models routinely abstract simultaneously from two features of the US federal tax code: the joint taxation of ordinary capital and labor income and the special taxation of preferential capital income. In this article, we argue that this abstraction omits a "portfolio-effect" mechanism where endogenous changes to the ordinary-preferential composition of households' capital income influence individuals' optimal labor and saving decisions through its impact on their effective marginal tax rates. We demonstrate the quantitative importance of this tax detail by simulating provisions from the recently enacted "Tax Cuts and Jobs Act" using a heterogeneous-agent overlapping generations framework calibrated to the US economy. Our findings imply that accounting for the detailed taxation of labor and capital income should be considered an important modeling feature for tax policy analysis.